Ligand-independent signals from angiotensin II type 2 receptor induce apoptosis - Miura, Shin-ichiro (Oxford University Press, 2000)
Conventional models of ligand–receptor regulation predict that agonists enhance the tone of signals generated by the receptor in the absence of ligand. Contrary to this paradigm, stimulation of the type 2 (AT(2)) receptor by angiotensin II (Ang II) is not required for induction of apoptosis but the level of receptor protein expression is critical. We compared Ang II-dependent and -independent AT(2) receptor signals involved in regulating apoptosis of cultured fibroblasts, epithelial cells and vascular smooth muscle cells. We found that induction of apoptosis—blocked by pharmacological inhibition of p38 mitogen-activated protein kinase and caspase 3—is a constitutive function of the AT(2) receptor. Biochemical and genetic studies suggest that the level of AT(2) receptor expression is critical for physiological ontogenesis and its expression is restricted postnatally, coinciding with cessation of developmental apoptosis. Re-expression of the AT(2) receptor in remodeling tissues in the adult is linked to control of tissue growth and regeneration. Therefore, we propose that overexpression of the AT(2) receptor itself is a signal for apoptosis that does not require the renin–angiotensin system hormone Ang II.